2003
DOI: 10.1038/sj.onc.1206500
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lymph node 64 (MLN64), a gene overexpressed in breast cancers, is regulated by Sp/KLF transcription factors

Abstract: MLN64, is invariably coamplified and coexpressed with erbB-2 in breast cancers. The human MLN64 and ERBB2 genes are positioned at less than 50 kb from each other, on chromosome 17q12. To understand the molecular basis of MLN64 overexpression in cancer, the genomic region containing the MLN64 and ERBB2 genes was isolated and mapped. The two genes, DARPP32 and Telethonin, flanking MLN64 respectively on its centromeric and telomeric sides, although coamplified, are not overexpressed in breast cancer cells, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 47 publications
1
34
0
1
Order By: Relevance
“…Ainsi, même dans les gonades mâles, l'expression des deux protéines ne se superpose pas, suggérant que la finalité du transport du cholestérol est différente même si le mécanisme molé-culaire est conservé. La protéine STARD15, un membre de la famille , est exprimé par tous les tissus -ce qui est corroboré par la présence dans le promoteur de STARD3 de séquences consensus typiques d'un promoteur ubiquitaire [29] -mais certains tissus comme le placenta l'expriment de façon plus importante [4]. Certains organes importants pour le métabolisme des lipides comme le foie, expriment la plupart des protéines START suggérant qu'il existe une redondance et/ou une coopération entre ces protéines dans cet organe.…”
Section: Mécanisme Moléculaire D'échange De Lipide Profil D'expressiounclassified
“…Ainsi, même dans les gonades mâles, l'expression des deux protéines ne se superpose pas, suggérant que la finalité du transport du cholestérol est différente même si le mécanisme molé-culaire est conservé. La protéine STARD15, un membre de la famille , est exprimé par tous les tissus -ce qui est corroboré par la présence dans le promoteur de STARD3 de séquences consensus typiques d'un promoteur ubiquitaire [29] -mais certains tissus comme le placenta l'expriment de façon plus importante [4]. Certains organes importants pour le métabolisme des lipides comme le foie, expriment la plupart des protéines START suggérant qu'il existe une redondance et/ou une coopération entre ces protéines dans cet organe.…”
Section: Mécanisme Moléculaire D'échange De Lipide Profil D'expressiounclassified
“…Like GRB7, MLN64 amplification as well as expression in human breast carcinomas closely correlates with HER2 (24). MLN64 and HER2 share similar transcriptional regulatory elements and both are activated by transcription factor SP1 (25). Genomic colocalization of nonhomologous genes that are coexpressed and involved in common biological processes has already been described in several organisms (24,26,27).…”
mentioning
confidence: 97%
“…To achieve a complex biological function, the coordinate expression of several clustered genes may be advantageous. Hence, it has been speculated that HER2, GRB7, and MLN64, located in the same chromosomal region, are involved in a common biological pathway (25). Accordingly, aberrant activation of each of these proteins in a subset of breast tumors might contribute to their poor clinical prognosis and outcome.…”
mentioning
confidence: 99%
“…However, full-length MLN64 is less active in steroidogenic assays since its transmembrane domain localizes it to late endosomes with the START domain facing the cytosol [8,10] . For this reason, the role of MLN64 in steroidogenesis is still unclear, but it has been suggested that proteolysis could release the START domain to allow delivery of cholesterol to mitochondria speculation that high levels of MLN64 observed in some breast carcinomas could contribute to the progression of these tumors through increased intratumoral steroidogenesis [4] . The localization and topology of MLN64 in late endosomes suggest that this protein participates in the efflux of cholesterol from late endosomes and lysosomes, possibly together with other proteins such as NiemannPick type C (NPC)1 and NPC2 [10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…Although MLN64 could play a causative role in tumorigenesis, its amplification probably reflects the close genomic proximity (within 36 kb) to the oncogene c-erb-B2 (her-2/ neu), which is invariantly coamplified [3,4] . The N-terminal of MLN64, the so-called MENTAL domain, includes four transmembrane helices, whereas the C-terminal domain contains the StAR-related lipid transfer domain (START) [5,6] .…”
Section: Introductionmentioning
confidence: 99%